Плакети и наградни значки на АРМ (1992-2019)- Plaques and Award Badges of the ARM 1992–2019 - Trajkov, Trajce (Македонски хералд - Macedonian Herald, 2020)
The article describes and presents the plaques and badges of the Army of the Republic of Macedonia (ARM) in accordance with the Rulebooks of 2003 and 2012 adopted by the President of the country. The 2003 Rulebook prescribes three Army plaques (small, medium and large) and one Army badge. The Rulebook from 2012, adopted on the eve of the 20th birthday of the ARM, is a significantly expanded and conceptually well-conceived set of military awards—one three-level plaque (small, medium, and large) and three three-level badges (Bronze, Silver, and Gold Badge of Army; Bronze, Silver, and Gold Badge of the Army for partnership, coordination and cooperation; Bronze, Silver, and Gold Badge for long service in the Army) awarded to civilian and military personnel serving in the ARM, as well as to citizens, institutions, and organizations honored for cooperation, support, and promotion of the Army. The Rulebook of 2012 significantly upgraded and expanded the Macedonian military-phaleristic system and thus filled the gap that existed in terms of military decorations in the Republic of Macedonia.